2016
DOI: 10.21123/bsj.2016.13.2.2ncc.0399
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cortisol and BMI in Chronic Diseases and Increased Early Cardiovascular Diseases

Abstract: The purpose of this study was to examine the role of cortisol, and it is related to BMI in the chronic diseases which may increase early cardiovascular disease (CVD) in old Iraqi. The subjects were 116 adults, aged 51-71 years. Body Mass Index (BMI), Waist Circumferences (WC) and Waist Hip Ratio (WHR) were used as a measure of adiposity. Investigation showed highly significant difference between patients in BMI ranges, most of male were in an obese weight range (48.5%), as well in women. There were no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Another study [27] showed a highly significant BMI with obesity. According to the GST results, there is a substantial difference in GST between these groups and obesity; these findings are consistent with earlier studies [28].…”
Section: Discussionmentioning
confidence: 95%
“…Another study [27] showed a highly significant BMI with obesity. According to the GST results, there is a substantial difference in GST between these groups and obesity; these findings are consistent with earlier studies [28].…”
Section: Discussionmentioning
confidence: 95%
“…High levels of serum cholesterol are recognized as a major risk for coronary heart disease and stroke [6]. About 80% of hypertensive patients have co morbidities such as fatty, glucose intolerance and abnormalities in lipid metabolism [4].The results of elevated total cholesterol in hypertensive patients agree with Adedji et al [15] and Goran et al [16]. There is a significant correlation between total cholesterol and systolic blood pressure, also between TG and diastolic blood pressure [17].In the present study, the higher plasma TC, TG and LDL levels in the patients than in the control group agrees with earlier studies [18].…”
Section: Lipid Profile Tests Study the Effect Of Duration Of Disease mentioning
confidence: 99%
“…It is the main risk factor for cardiovascular disease, congestive cardiac failure, stroke and end-stage of kidney disease [3]. Hypertension is one of manifestation of metabolic syndrome [4]. High blood pressure and dyslipidemia are main risk factors for coronary heart disease and account for more than 80% of death disability in low and middle -income countries [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is the main risk factor for cardiovascular disease, congestive cardiac failure, stroke and endstage of kidney disease (Casey et al, 2006). Hypertension is one of manifestation of metabolic syndrome (Hassan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%